EFFECT OF INTEGRATED NUTRIENT MANAGEMENT ON YIELD, QUALITY AND NUTRIENT UPTAKE OF ISABGOL (PLANTAGO OVATA) - INDRA, CHOUDHARY; SHIVRAN, A.C. (Annals of Agricultural Research, 2014)
A field experiment comprising six levels of fertilizers/manures and three biofertilizers was conducted in randomized block design and replicated three at Agronomy farm, S.K.N. College of Agriculture, Jobner (Rajasthan) during rabi, 2005-06 on loamy sand soil. Results showed that application of vermicompost @ 1 .5 t/ha + 50% RDF significantly increased seed and straw yields and total NPK uptake over control, RDF, FYM @ 8.0 t/ha, vermicompost @ 3.0 t/ha ana FYM @ 4.0 t / ha + 50% RDF. Protein content and swelling capacity were also significantly increased with application of fertilizers/manures except FYM @ 8.0 t/ha and maximum was recorded under vermicompost @ 1.5 t/ha + 50% RDF. Organic carbon and available NPK in soil at harvest of the crop were significantly higher with application of fertilizers/manures. Results further revealed that seed and straw yields, total NPK uptake and available N content in soil at harvest were significantly higher with inoculation due to Azotobacter as well as Azospirillum over control.